Regional disparities in India - Goswami A. 1937-.; Omeo Kumar Das Institute of Social Change and Development (Gauhati, India).; National Workshop on Regional Disparities Gauhati, India) (1996. (New Delhi Akansha Pub. House, 2001)
Contributed articles presented in a National Workshop on Regional Disparities organised by the Omeo Kumar Das Institute of Social Change and Development, Guwahati, during 1996.
Keywords: India -- Economic conditions -- Regional disparities